A Three Year Study of Skull Fracture Patterns in Fatal Road Traffic Accidents in a Tertiary Care Hospital Mortuary in Imphal From 2015-2018 (Medico Legal Update, 2020)
Fatal road traffic accident cases with skull fractures were studied for three years from July 2015 to June 2018 from the medicolegal autopsy cases coming to the Mortuary of the Regional Institute of Medical Sciences, Imphal. The patterns of skull fractures in various types of victims involved in accidents with different types of vehicles were analyzed in detail. It was observed that skull fractures were encountered most commonly in pedestrian victims.Of the various types of skull fractures, comminuted fracture was observed in maximum number of cases (31.5%). Preventive and interventional measures in the form of wearing helmets by two wheeler riders ,strict implementation of traffic rules and prompt emergency services especially neurosurgery facilities which can help in reducing the incidence of road traffic accident fatalities are suggested.